Identification of the main active ingredients of agrochemicals used around the Lake of Tota, Colombia - Pérez-Holguín, Wilson Javier; Grandas-Rincón, Isnardo Antonio; Ramírez-Acevedo, Lizeth Natalia; Torres-Barrera, Nixon Hernán (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper presents a descriptive study aimed at identifying the main active ingredients, frequency of use, and the processes employed in the application of the agrochemicals most used around the Lake of Tota, which is considered the most important freshwater ecosystem in Colombia. A key source for this study is a survey to farmers, which sampling frame was established from a Geographical Institute Agustin Codazzi (IGAC) digital map, considering only the plots with some agricultural activity and runoff into the lake. This information was supplemented with geographic data obtained from Google Maps®. As control mechanism, two additional sources were used: i) a manual count of packaging of agrochemicals in a certified collection center, and ii) a census of stores that supply such products in the study area. The results allow knowing the set of agrochemicals most used around the lake, their active ingredients, and the most common farming practices, some of which could entail some risk to farmers, consumers and the environment.